Peripherally Hexasulfanylated Subporphyrins. Issue 7 (15th April 2015) - Yoshida, Kota; Osuka, Atsuhiro
Abstract Peripherally hexachlorinated meso‐triphenyl subporphyrin 4 was prepared by chlorination of meso‐triphenyl subporphyrin 1 with N‐chlorosuccinimide and was effectively transformed to hexasulfanylated subporphyrins 5–8 via nucleophilic aromatic substitution (SNAr) reactions with the corresponding thiols under basic conditions. The structures of 5–8 have been all well characterized by single‐crystal X‐ray analysis. 1H NMR studies indicated that the meso‐phenyl substituents undergo restricted rotation for 5–8, while the β‐sulfanyl substituents are conformationally flexible in 5, 6, and 8, and are strictly regulated to an anti‐conformation in 7. Judging from the absorption spectra, the oxidation and reduction potentials, and the DFT calculations, the substituent effects decrease in the order of 5>6>7>8. Subporphyrin 8 effectively captures C60 in a 1:1 manner in [D8]toluene solution.